The role of macroeconomic factors in shaping employment trends in Somalia - Abdikadir Ahmed Mohamed; Abdikani Yusuf Abdulle; Mahdi Mohamed Omar (Cogent Economics & Finance, 2024)
Somalia has one of the most severe unemployment rates globally, due to its economic instability. Our study focuses on the macroeconomic effects on employment using an ARDL model. The key macroeconomic variables examined are GDP, inflation, FDI, foreign aid, and population growth, with data sourced from the World Bank spanning 32 years, from 1991 to 2022. The study found that GDP positively affects employment in both the short and long run. Inflation shows a positive correlation with employment in the short run but a negative effect but insignificant in the long run. FDI has a positive effect in the long run and a negative, insignificant effect in the short run. Foreign aid positively impacts employment in both the short and long run, though the effect is not significant in the latter. the study recommends policies to sustain economic growth, manage population growth, stabilize prices, and improve aid management to enhance employment opportunities in Somalia. This research examines the macroeconomic determinants of employment in Somalia, focusing on the effects of economic growth, inflation, foreign direct investment (FDI), foreign aid, and population growth from 1991 to 2022. Using an ARDL model, the study provides both short-term and long-term insights into how these factors influence employment trends. The findings underscore the positive role of GDP growth and foreign aid in promoting employment, while highlighting the negative impact of rapid population growth on job creation. This work is significant as it offers targeted policy recommendations to address Somalia's unemployment challenges, emphasizing the need for sectoral diversification, improved governance of foreign aid, and strategies to stabilize FDI flows. The study provides a vital contribution to the limited literature on Somalia's employment dynamics and serves as a guide for policymakers working to foster sustainable economic growth and job creation.
Keywords: 330; ARDL; economic growth; Employment; FDI; inflation; macroeconomic; population growth; Somalia